The Concept of Smart Economy as the Basis for Sustainable Development of Ukraine - Galperina, Liubov Pavlivna; Girenko, Anna Tymofiyivna; Mazurenko, Valentyna Petrivna (International Journal of Economics and Financial Issues, 2016)
The relevance of the research is closely connected with the need to develop effective instruments for sustainable development of Ukraine. The purpose of the article is to generalize theoretical foundations of analysis of the concept of reasonable economy to determine strategic measures aimed at maintaining sustainable development of Ukraine and its empirical verification. The leading method of the research is the usage of the Pressure-State-Response (PSR) model for analysis of interaction of indicators common in characterization of smart economy and sustainable development. The indicators were selected taking into account the specific character of modern economic development of Ukraine. This approach is based on the concept of sustainable development considered in the context of smart economy. Using multiple regression analysis the impact of smart economy's factors is evaluated, sorted according to the PSR model, on the total greenhouse gas emissions (dependent variable) in Ukraine. The results of the model evaluation allowed to identify two factors that have the greatest impact on the total greenhouse gas emissions in Ukraine: GDP per employed person and the level of energy intensity of primary energy. It allowed to justify the priority of such strategic means as the stimulation of innovations, the smart economy and the promotion of green economy. They are the general indicators of the smart economy and affect the sustainable economic development of Ukraine nowadays. The research findings have the practical value for those who determine policies aimed at resolving problems of sustainable development at the appropriate level. Keywords: Smart economy; sustainable development, innovation network; Ukraine. JEL Classification: F4